The relationship between cyberloafing and task performance among employee at Jabatan Imigresen Negeri Johor / Saidah Suhaila Saharudin - Saharudin, Saidah Suhaila (2014)
Research has found that cyberloafing is not too influence more to task performance in Jabatan lmigresen Negeri Johor. This study reports is about factors of cyber loafing among employee task performance at this organization. However, studies have shown that Counter productive work behaviors have been studied extensively, but much less work has been done on cyber loafing - the personal use of the internet at work. The theoretical framework for this study is based on conceptual framework. Three factors representing independent variables that contributes to the cyber loafing and task performance. Data are gathered through surveys staff in Jabatan Imigresen Negeri Johor which implemented cyberlaofing. The purpose of this research is to identify what are the highest factors that lead to employees' cyberloafing at Jabatan Imigresen Negeri Johor and to identify the consequences of cyberloafing to task performance. The results show that there have both positive and negative relationships between cyberloafing and task performance among employee at Jabatan lmigresen Negeri Johor.